Hybrid B1+‐shimming and gradient adaptions for improved pseudo‐continuous arterial spin labeling at 7 Tesla. Issue 1 (19th August 2021) - Meixner, Christian R.; Eisen, Christian K.; Schmitter, Sebastian; Müller, Max; Herrler, Jürgen; Hensel, Bernhard; Dörfler, Arnd; Uder, Michael; Nagel, Armin M.
Abstract : Purpose: To improve pseudo‐continuous arterial spin labeling (pcASL) at 7T by exploiting a hybrid homogeneity‐ and efficiency‐optimized B 1 + ‐shim with adapted gradient strength as well as background suppression. Methods: The following three experiments were performed at 7T, each employing five volunteers: (1) A hybrid (ie, homogeneity‐efficiency optimized) B 1 + ‐shim was introduced and evaluated for variable‐rate selective excitation pcASL labeling. Therefore, B 1 + ‐maps in the V3 segment and time‐of‐flight images were acquired to identify the feeding arteries. For validation, a gradient‐echo sequence was applied in circular polarized (CP) mode and with the hybrid B 1 + ‐shim. Additionally, the gray matter (temporal) signal‐to‐noise ratio (tSNR) in pcASL perfusion images was evaluated. (2) Bloch simulations for the pcASL labeling were conducted and validated experimentally, with a focus on the slice‐selective gradients. (3) Background suppression was added to the B 1 + ‐shimmed, gradient‐adapted 7T sequence and this was then compared to a matched sequence at 3T. Results: The B 1 + ‐shim improved the signal within the labeling plane (23.6%) and the SNR/tSNR increased (+11%/+11%) compared to its value in CP mode; however, the increase was not significant. In accordance with the simulations, the adapted gradients increased the tSNR (35%) and SNR (45%) significantly. Background suppression further improved the perfusion images at 7T, and this protocol performed as well as a resolution‐matched protocol at 3T. Conclusion: The combination of the proposed hybrid B 1 + ‐phase‐shim with the adapted slice‐selective gradients and background suppression shows great potential for improved pcASL labeling under suboptimal B 1 + conditions at 7T.